Strong Near-infrared Emission Following the Long-duration GRB 211211A: Dust Heating as an Alternative to a Kilonova - Eli Waxman; Eran O. Ofek; Doron Kushnir (The Astrophysical Journal)
The prolonged near-infrared (NIR) emission observed following the long-duration GRB 211211A is inconsistent with afterglow emission from the shock being driven into the circumstellar medium (CSM) as well as with emission from a possible underlying supernova. It has therefore been suggested that the observed NIR flux is the signature of a kilonova—a radioactive ejecta that is similar to the outcome of the binary neutron star merger GW170817. We propose here an alternative plausible explanation. We show that the NIR flux is consistent with thermal emission from dust, heated by UV and soft-X-ray radiation produced by the interaction of the gamma-ray-burst (GRB) jet plasma with the CSM. This NIR emission was predicted by Waxman & Draine for GRBs residing near or within massive molecular clouds. The dust NIR emission scenario is consistent with a GRB at z  ≲ 1. Inspection of the environment of GRB 211211A suggests that there are at least two host galaxy candidates, one at z = 0.076 and the other at z = 0.459. The z = 0.459 possibility is also consistent with the nondetection of a supernova signature in the light curve of the GRB afterglow as well as with the typical GRB gamma-ray energy for the fluence of GRB 211211A.